Case Report: Co-occurrence of Myocarditis and Thrombotic Microangiopathy Limited to the Heart in a COVID-19 Patient - Menter, Thomas; Cueni, Nadine; Gebhard, Eva Caroline; Tzankov, Alexandar (Frontiers in Cardiovascular Medicine, 2021)
We report on an impressive case of a previously healthy 47-year-old female Caucasian SARS-CoV-2 positive patient, who died within 48 hours after initial cardiac symptoms. Autopsy revealed necrotizing myocarditis and extensive microthrombosis as the cause of death. The interesting feature of this case is the combination of both myocarditis and extensive localized microthrombosis of cardiac capillaries. Microthrombosis was not present in other organs and the patient did not show typical features of diffuse alveolar damage in the lungs. Taken together, our morphologic findings illustrate the angiocentric, microangiopathic, thromboinflammatory disease with significant thrombotic diathesis prevalent in COVID-19, which has been previously described in the literature, likely warranting thromboprophylaxis even in oligosymptomatic circumstances. This case also delineates several potential etiologies for microthrombosis: i.e. inflammatory reactions and primary hypercoagulative states. Further systematic analyses on risk stratification for receipt of prophylactic anticoagulation in COVID-19 are urgently required.